Interaction between Two Inclined Cracks in Bonded Dissimilar Materials subjected to Various Stresses - Hamzah K.B.; Nik Long N.M.A.; Senu N.; Eshkuvatov Z.K. (IOP Publishing Ltd, 2024)
Indexed by Scopus/ERA